About Development Regulation of Small-Scale Agrarian Business Entities in the South of Russia - TOLMACHEV, Aleksey Vasilevich; MELNIKOV, Alexander Borisovich; BERSHITSKIY, Yuriy Iosifovich; VASILIEVA, Nadezhda Konstantinovna; ARTEMOVA, Elena Igorevna (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The objective of the study is to clarify the definition of ‘small-scale agrarian business entities’ (SABE), to develop the provisions concerning the effective functioning and regulation of SABE development. A methodological basis of the study included scientific works on managing the processes of the functioning, development and regulation of SABE activity, recommendations of scientific organizations, the normative and legal basis of the Russian Federation legislation and its subjects. In the paper, the principles of system-functional analysis, methods of rationale and statistical analysis, monographic analysis, SWOT-analysis, graphical methods and others were used. The authors’ definition of ‘small-scale agrarian business entities’ differing from the definition ‘small-scale business entities in agriculture’, which is widely used in scientific and manufacturing practice, was proposed. Peculiarities of the functioning and regulation of SABE development were specified and systematized, which allows using the advantages, strengths, growth reserves of SABE, taking into account the risks of their development. Modern competitive SABE opportunities, characterized by the lack of market power, limitations of market capacities, sale problems, diversity of organizational and legal forms, inaccessibility to credit resources, lack of investment, dependency on local conditions, the need for cooperation and others, were revealed and systematized.